Acmeological-conceptual model of productive activity for primary school teachers - Jakobchuk, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
This article denotes the acmeological specifics about productive teachers of primary classes. The author uses acmeological conceptual model of the productive activity of teachers of initial classes with the purpose of overcoming the negative contradictions in the course of the research. It is offered to create the bank of acmeological information on performance models, tools, situations of self-improvement.
Keywords: acmeology; acmeological approach; productive activities; criteria of professional activity